The History of Emotions in Australia. Issue 1 (2nd January 2017) - Pinto, Sarah
Abstract : In the last two decades, emotions have increasingly featured in Australian historical scholarship. This article reviews the history of emotions in Australia by examining the various ways in which historians have engaged with and mobilised the emotions in their research. It argues that, for most Australian historians, the emotions are a tool of investigation in projects with historical interests that are largely directed elsewhere. Historical scholarship in Australia suggests, then, that the emotions are most useful as a category of analysis in the service of a range of other historical agendas.